Program“Jari Peri” sebagai Pelindung Anak dari Kekerasan Seksual - Indah Islawati; Ira Paramastri (Jurnal Psikologi, 2015)
child sexual Abuse (CSA) is a form of violation against children's rights and it leads to various negative effects on them. In order to protect them, it is necessary to conduct primary prevention by developing teachers to be CSA-preventing agents. Therefore, they need good self-efficacy in teaching about the issues that their students will be able to comprehend it well. This study aimed to observe the improvement of teachers’ self-efficacy related to their teaching of the issue. This study used a quantitative research method with the untreated control group design with a dependent pretest and posttest sample. The subjects of this research were elementary schoolteachers chosen purposively. Mixed ANOVA analysis was used to measure the increase of teachers’ self-efficacy in teaching this issue to their students. The self-efficacy of teachers in the experiment group was higher than those in the control group.